Global warming induced changes in the means and extremities of temperature and precipitation in Hungary - Mike, János; Lakatos, Mónika (Journal of Environmental Geography, 2009)
Regional climate changes are still one of the most difficult problems of the climate change issue. Results by three scientific approaches, the raw General Circulation Models (GCM), the mesoscale models, compiled from the PRUDENCE project, and an empirical method, called Natural experiment are compared. The latter approach provides estimations of the future changes based on regression coefficients between the local and global variables in the monotonously warming 1976-2007 period. The global model results comprise results of 9 AOGCMs, whereas in the PRUDENCE set of 5 model outputs are analysed. The listed results start with changes in the seasonal temperature and precipitation averages. Here the signs and the magnitudes are similar according to all approaches: Faster than global mean temperature increases in all seasons, with strongly decreasing precipitation in summer and autumn but increased amounts in winter and spring. There is also a fair agreement of the three approaches in the temperature extremes of the warm half-year in Hungary, with much less unequivocal picture in the frequency of frozen days in the cold half of the year. For precipitation, again, the summer maxima of diurnal totals behave similarly according to the three approaches in all regions of the country. Namely, they exhibit unequivocal increase, whereas no clear picture is seen for frequency of wet/dry days.